The creation of architectural facades using Midjourney artificial intelligence - Trujillo-Quispe, Rafael (2024)
The objective of this article is to present the virtues offered by a design strategy based on the use of artificial intelligence for the creation of architectural facades. The aim is to explore how the use of new technologies influences a specific field in order to propose a hypothesis of how it will affect the field of architecture in the future. They will be able to know and develop the potential of using the software and how it facilitates not only the creation of the "form" of the façade but also the facilities it provides to the designer when applying it, since it is mistakenly believed that this type of tool It is difficult to run and requires an expensive computer.